Expression and Function of Transmembrane-4 Superfamily (Tetraspanin) Proteins in Osteoclasts: Reciprocal Roles of Tspan-5 and NET-6 during Osteoclastogenesis - Kaori Iwai; Masaru Ishii; Shiro Ohshima; Kunio Miyatake; Yukihiko Saeki (Allergology International, 2007)
Background: Osteoclasts are bone-resorbing multinuclear polykaryons essential for bone remodeling, formed through cell fusion of mononuclear macrophage/monocyte lineage precursor cells upon stimulation by the RANK/RANKL system. Recent studies have revealed that a family of tetraspanin proteins, such as CD9, is critically involved in the cell fusion/polykaryon formation of these cell types. Until now, however, there is limited knowledge about the types of tetraspanins expressed in osteoclasts and their precursors. Methods: The expression of different tetraspanin proteins in a monocyte/macrophage-lineage osteoclast precursor cell line, RAW264.7, was cyclopedically investigated using RT-PCR with specific primers and quantitative real-time RT-PCR. The function of two kinds of tetraspanins, Tspan-5 and NET-6, whose expression pattern was altered by RANKL stimulation, was examined by transfecting gene-specific short-interfering RNAs into these cell types. Results: Of the 17 tetraspanins in mammalian hematopoietic cells, RAW264.7 cells express mRNA for 12 different kinds of tetraspanins, namely, CD9, CD37, CD53, CD63, CD81, CD82, CD151, NAG-2, NET-6, SAS, Tspan-3, and Tspan-5. Interestingly, during their maturation into osteoclasts upon RANKL stimulation, the transcript for Tspan-5 is up-regulated, whereas that for NET-6 is down-regulated. Targeted inhibition of Tspan-5 by using gene-specific RNA interference suppressed RANKL-induced cell fusion during osteoclastogenesis, whereas inhibition of NET-6 augmented the osteoclastogenesis itself. These results suggest that Tspan-5 and NET-6 have a reciprocal function during osteoclastogenesis, i.e., positive and negative regulation by Tspan-5 and NET-6, respectively. RANKL regulates osteoclastogenesis by altering the balances of these tetraspanin proteins. Conclusions: These data indicate that a diversity of tetraspanins is expressed in osteoclast precursors, and that cell fusion during osteoclastogenesis is regulated by cooperation of distinct tetraspanin family proteins such as Tspan-5 and NET-6. This study indicates that functional alterations of tetraspanin family proteins may have therapeutic potential in diseases where osteoclasts play a major role, such as rheumatoid arthritis and osteoporosis.